Virulence-determinants and antibiotic-resistance genes of MDR-E. coli isolated from secondary infections following FMD-outbreak in cattle - Algammal, Abdelazeem M.; Hetta, Helal F.; Batiha, Gaber E.; Hozzein, Wael N.; El Kazzaz, Waleed M.; Hashem, Hany R.; Tawfik, Ayat M.; El-Tarabili, Reham M. (Scientific reports, 2020)
This study aimed to evaluate the prevalence, multidrug-resistance traits, PCR-detection of virulence, and antibiotic-resistance genes of E. coli isolated from secondary infections following FMD-outbreak in cattle. A total of 160 random samples were gathered from private dairy farms in Damietta Province, Egypt. The specimens were subjected to bacteriological examination, serotyping, congo-red binding assay, antibiogram-testing, and PCR-monitoring of virulence-determinant genes ( tsh , pho A, hly , eae A, sta , and lt ) as well as the antibiotic-resistance genes ( bla TEM , bla KPC , and bla CTX ). The prevalence of E. coli was 30% (n = 48) distributed in 8 serogroups (40/48, 83.3%), while 8 isolates (8/48, 16.6%) were untypable. Besides, 83.3% of the examined isolates were positive for CR-binding. The tested strains harbored the virulence genes pho A, hly , tsh, eae A, sta , and lt with a prevalence of 100% and 50%, 45.8%, 25%, 8.4%, and 6.2%, respectively. Furthermore, 50% of the recovered strains were multidrug-resistant (MDR) to penicillins, cephalosporins, and carbapenems, and are harboring the bla TEM , bla CTX , and bla KPC genes . Moreover, 25% of the examined strains are resistant to penicillins, and cephalosporins, and are harboring the bla TEM and bla CTX genes. To the best of our knowledge, this is the first report concerning the E. coli secondary bacterial infections following the FMD-outbreak. The emergence of MDR strains is considered a public health threat and indicates complicated treatment and bad prognosis of infections caused by such strains. Colistin sulfate and levofloxacin have a promising in vitro activity against MDR- E. coli .